Manajemen Mutu Pendidikan Islam Dalam Perspektif Al-Qur’an dan Hadits - Fathurrohman, Muhammad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2018)
Quality is important to be undertaken by an educational institution, especially institutions of Islamic education. Because quality is something addressed in the management of Islamic educational institutions. Management generally has a lot of the concept of quality, but the concept of quality in Islamic educational management is little. Therefore, formulating and underlying concepts of quality in Islamic educational management becomes important. Quality is always associated with customers, stakeholders, and users of products or services produced by an organization or individual. Quality is a measure used to assess the process and product. However, the quality is usually determined by the customer, not the supplier. The concept of quality in management education can be synchronized with the Islam of the Koran and al-Hadith. The Koran and al-Hadith provide cues about quality in everything with the word ihsan. Ihsan means quality. If applicable and explained, apparently Ihsan has implications for the quality of the process, the quality of the planning and control, which in turn produces quality development frameworks according to al-Qur'an and al-hadith. Keywords: Quality management, Islamic education, Al Quran-hadits.